Model of Empowerment Arad Nets Fisherman Towards Responsible Fisheries to Improve The Welfare of Fishermen - Sulistyowati, Sulistyowati (Universitas Muhammadiyah Semarang, 2017)
This study aims to describe the profile of fishermen, Arad's empowerment strategy, and model of empowerment of fisherman of Arad net to